Discovering Differences in Consciousness of Facial Features Among Japanese University Students in the Year of Admission According to COVID-19 - Komiya, Nozomi (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to determine the significant differences in students' awareness of appearance between those admitted to universities during the COVID-19 pandemic and those admitted when the pandemic was deemed controlled in Japan. Methodology: The author hypothesized notable variations in the change of self-consciousness regarding appearance, particularly facial appearance, contingent upon the year of admission. To test this hypothesis, a questionnaire survey was conducted among 428 students in Japan attending universities as of Fiscal Year 2023 to gauge their facial self-consciousness. Main Findings: The initial analysis focused on changes in body image and facial self-consciousness. However, due to the predominant focus on facial aspects, a chi-squared test was allowed to determine the relationship between the year of admission and changes in facial self-consciousness. The results indicated a significant difference between the admission year and changes in facial self-consciousness, with the largest difference between 2020 and 2023. Novelty/Originality of this study: The author used Cross-tabulation and Chi-Square analyses to compare previous years with 2023. The findings showed significant differences in facial self-consciousness depending on the admission year, with a p-value of less than 0.05. The results indicated statistically significant differences in facial self-consciousness among students admitted in 2020. (p < .05, =.005, =.014, =.016).